2015
DOI: 10.1089/aid.2014.0121
|View full text |Cite
|
Sign up to set email alerts
|

Designed Transcription Activator-Like Effector Proteins Efficiently Induced the Expression of Latent HIV-1 in Latently Infected Cells

Abstract: HIV latency is the foremost barrier to clearing HIV infection from patients. Reactivation of latent HIV-1 represents a promising strategy to deplete these viral reservoirs. Here, we report a novel approach to reactivate latent HIV-1 provirus using artificially designed transcription activator-like effector (TALE) fusion proteins containing a DNA-binding domain specifically targeting the HIV-1 promoter and the herpes simplex virus-based transcriptional activator VP64 domain. We engineered four TALE genes (TALE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The presence of residual latent but replication-competent HIV-1 reservoirs is a major hurdle impeding viral eradication. Recent work has indicated that HIV expression can be induced using zincfinger 83 and TAL effector-based 84 transcription factors engineered to bind the LTR promoter. Here, we show that CRISPR/Cas9based transcriptional effectors-which can be retargeted to nearly any DNA sequence without protein engineering-can reactivate viral gene expression in cell line models of HIV-1 latency.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of residual latent but replication-competent HIV-1 reservoirs is a major hurdle impeding viral eradication. Recent work has indicated that HIV expression can be induced using zincfinger 83 and TAL effector-based 84 transcription factors engineered to bind the LTR promoter. Here, we show that CRISPR/Cas9based transcriptional effectors-which can be retargeted to nearly any DNA sequence without protein engineering-can reactivate viral gene expression in cell line models of HIV-1 latency.…”
Section: Discussionmentioning
confidence: 99%
“…However, it cannot eliminate the integrated HIV-1 genome, and CCR5 is not the sole receptor for HIV-1 infection and has many other cellular functions as well[20]. The highly conserved HIV-1 LTR has been targeted by ZFN and TALEN for the eradication of the integrated HIV-1 genome[24-26]. The major drawbacks for ZFNs and TALENs are the tedious engineering of custom DNA-binding fusion proteins for each target site, which limit their universal application and clinical safety[27-30].…”
Section: Introductionmentioning
confidence: 99%
“…Like ZFPs, TALENs have been used to knock out the CCR5 gene in cell culture [203][204][205][206], permitting efficient gene editing and protection of cells from HIV infection [207] with minimal off-target activity and low cytotoxicity. TALE-activators, corresponding to TALEs fused to potent transcription activators, have been developed and shown to effectively reactivate latent HIV-1 in cell line models [208][209][210] and in PBMCs from ART-suppressed individuals [210]. TALE technology combines several features that are quite favorable for gene editing applications.…”
Section: Talesmentioning
confidence: 99%